Provincial solidarities : a history of the New Brunswick Federation of Labour - Frank, David, 1949- (Working Canadians (Edmonton, Alta.) ;, 2013)
Provincial Solidarities tells the story of the New Brunswick Federation of Labour--part of the history of working class struggles in Canada.